Stone soup - Muth, Jon J (Scholastic Press, 2003)
This book is about three strangers, hungry and tired, traveling through a war-torn village. Depressed and suspicious because of the war, people hid food and tightly closed their windows. That is until clever strangers offered to cook a soup from rocks. Intrigued by the idea, everyone brought what they had until-- together, they created a feast fit for a king! In this inspiring story about the power people possess when working together, Muth takes a simple, beloved story and adds her own fresh twist.